IMMUNOPROTECTIVE EFFECT OF MELATONIN ADMINISTRATION ON METHYLPREDNISOLONE-TREATED WISTAR MALE RAT (RATTUS NORVEGICUS) - Widya Christine Manus; Wimpie Pangkahila; I Gusti Made Aman (Berkala Ilmiah Kedokteran Duta Wacana, 2019)
Background: Immune system function decreases with age. Steroid use might accelerate this process, especially in adults in Indonesia. Melatonin is a natural hormone which show antioxidant effect and immunoprotective effect. Melatonin administration might help in reviving humane immune system due to aging and exogenous steroid exposure. Objective: This experiment is aimed to determine the effect of melatonin on leukocyte and lymphocyte count of methylprednisolone-induced immunosuppression on Wistar rat. Method: This study was true experimental with post-test only control group design using 32 male rats. Rats were divided into control and the intervention group. Control group was given methylprednisolone 0.144 mg/200 g rat 3 times a day and distilled water. The treatment group was given methylprednisolone 0.144/200 g rat 3 times a day and 0.054 mg/200 g melatonin once daily. The blood was taken after 14 days of treatment. Results: Intervention group shows higher lymphocytes count (4.95 ±1.58x103/L) compared to the control group (3.091.33x103/L), with p < 0.01. The intervention group also has higher leukocyte count (8.37± 2.02x103/L) compared to the control group (6.70 ± 1.96x103/L), with p